Development of a p-type Silicon Interdigitated Back Contact Solar Cell With Passivated Contacts - Rachdi, Lazhar; Meßmer, Marius; Comak, Mertcan; Lossen, Jan; Wolf, Andreas; Koduvelikulathu, Lejo Joseph (SiliconPV Conference Proceedings, 2026)
P-type interdigitated back contact (pIBC) solar cells represent a promising alternative to the currently dominant Tunnel Oxide Passivated Contact (TOPCon) technology, utilizing the industrially established metallization scheme of Passivated Emitter and Rear Cells (PERC) for the p-type base while incorporating TOPCon metallization for the n-type polycrystalline emitter. In this study, we present the results of optimization efforts aimed at increasing the efficiency pIBC cells manufactured in our lab by minimizing metallization-induced losses. Aluminum pastes with varying silicon content were used, and the firing temperature was adjusted. These modifications resulted in a reduction in the metallization-induced Voc​ loss after aluminum metallization to 5 mV, along with contact resistance values below 1 mΩ.cm². Additionally, reducing the n-polySi thickness led to a decrease in free carrier absorption and an increase in Jsc​. Finally, we achieved non-metallized cell precursors exhibiting iVoc​ values between 730 and 740 mV and a champion solar cell efficiency of 23.3%.